A Perception and knowledge of Covid 19 in Indonesia: An intervention study : Perception and knowledge of Covid 19 in Indonesia: An intervention study - Eppy Setiyowati; Ni Njoman Juliasih; Reny Mareta Sari; Priyo Susilo (Jurnal Ilmiah Kesehatan, 2022)
more deeply about the awareness in healthy behavior and covid prevention 19. Coronavirus 2019 (Covid 19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV2), in Indonesia corona virus transmission still occurs in the community, a total of cases, 49.009 (at time of writing). The purpose of this study is the effect of selfmanagement education on changes perceptions and knowledge transmission covid 19 patients in hospital at East Java. Data were obtained from 150 patients coming to clinic clinics in East Java, since December 2019 - May 2020. Sampling through simple random sampling technique. Pretest data collection to identify perceptions and knowledge, then the intervention of selfmanagement education was carried out and finally posttest conducted. Pretest and posttest data collection included closed questionnaire, data analysis was performed with independent T test. Changes of perception after intervention selfmanagement education was to treatment group. Selfmanagement educationable to change the perception and knowledge of patients about covid transmission 19. In the future it is necessary to research